Internal and External Drivers of Ijon Transactions in Clove Farming: Evidence From Kotabunan Village, East Bolaang Mongondow - Mokobombang, M.Alfa Riski; Karundeng, Frandy Efraim Fritz (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2025)
This study aims to analyze the internal and external factors behind the practice of buying and selling transactions of the ijon system in clove farmers in Kotabunan Village, East Bolaang Mongondow Regency. The research uses a qualitative approach with a field descriptive method. Data was collected through direct observation, structured interviews with farmers, permit buyers, and village officials, as well as supporting documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion. The results of the study show that the buying and selling practice of the permit system is influenced by two main groups of factors. Internal factors include the urgent need to meet basic needs, farmers' dependence on permit buyers, the desire to make quick profits, and low Islamic financial literacy. Meanwhile, external factors include hereditary transaction culture, the influence of reference groups such as middlemen and fellow farmers, and uncertainty about clove prices in the market. The ijon system was chosen as a strategy to survive price fluctuations and the risk of harvest costs, even though in fiqh muamalah, it contains elements of gharar due to the uncertainty of the transaction object. This study concludes that Ijon practices are not solely driven by individual economic motives, but also by strengthened social and cultural structures at the community level. Therefore, this study recommends strengthening Islamic financial literacy, providing alternative access to capital, and community-based institutional interventions to reduce farmers' dependence on the ijon system and improve rural economic justice.